Perbaikan Model Peramalan dan Model Persediaan Reagen Kimia di PT. OPQ Untuk Mendapatkan Persediaan Optimum - Paduloh, Paduloh; Puspaningrum, Yunita; Yunita, Ika (Proceeding Mercu Buana Conference on Industrial Engineering, 2021)
Performing forecasts accurately and have optimal supplies are very urgent demands for most industries today. PT OPQ is a company engaged in the pharmaceutical industry. This industry produces medicines for both OTC (Over Counter), ethical (prescription drugs), and generics. At PT OPQ, the inventory method for chemical reagents that have been carried out is straightforward; each year only adds a certain quantity from the previous year. This method proved to be less effective and efficient because the use of chemical reagents was not certain, which resulted in the chemical reagent stock experiencing advantages and disadvantages as seen from the stock on hand. This research aims to assist companies in determining the amount of chemical reagent usage and controlling chemical reagent supplies optimally. The method used is forecasting with the ARIMA model; after obtaining the forecasting results, calculations are carried out to obtain optimal inventory results, namely the EOQ method. In this study, a differencing process was also carried out so that the data used were stationary. The study results obtained a forecasting model that is close to the actual conditions in the field. This study also produces an ideal safety stock for the company. The results of calculations using the EOQ method are proven to be far more optimal than the method previously applied by the company